Normative data for the 6-min walk test in 11-14 year-olds: a population-based study - Kasović, Mario; Štefan, Lovro; Petrić, Vilko (BMC pulmonary medicine, 2021)
BACKGROUND: The 6-min walk test (6MWT) has become an established measure for assessing exercise capacity in children with chronic diseases. However, little evidence has been provided regarding population-based normal data in healthy children. The main purpose of the study was to provide normative data in a large sample of children. METHODS: In this cross-sectional study, 4352 children between 11 and 14 years were recruited (66% girls). The main outcome measure was the distance walked for six minutes. Sex- and age-specific percentile values (5th, 15th, 25th, 50th, 75th, 85th and 95th) for the 6MWT were created and the differences and correlations were examined by the analysis of variance and Pearson's coefficient of correlation. RESULTS: The mean distance walked in 6 min was 576 ± 93 m in boys and 545 ± 92 m in girls, respectively. The mean walking speed for boys and girls was 98 ± 5 m/min and 91 ± 6 m/min. Older boys and girls performed better, compared to their younger counterparts (p for age < 0.001). The 6MWT was significantly correlated with age (r = 0.24, p < 0.001), height (r = 0.09, p < 0.001), weight (r = - 0.13, p < 0.001) and body-mass index (r = - 0.26, p < 0.001). CONCLUSIONS: This is the first population-based study aiming to provide normative data for the 6MWT in healthy children between 11 to 14 years. Children in lower percentiles are 'target groups' for special intervention aiming to enhance the performance.
Keywords: Walk Test; index tělesné hmotnosti; Cross-Sectional Studies; Pediatric; mladiství; sexuální faktory; mužské pohlaví; Standards; regresní analýza; průřezové studie; Body Mass Index; dítě; Walking; Child; složení těla; věkové faktory; Testing; referenční hodnoty; ženské pohlaví; test chůzí; chůze; Humans; Reference Values; Exercise capacity; Sex Factors; Age Factors; Body Composition; Regression Analysis; Female; Adolescent; lidé; Male